2014
DOI: 10.1161/strokeaha.113.003077
|View full text |Cite
|
Sign up to set email alerts
|

ABCD3 and ABCD3-I Scores Are Superior to ABCD2 Score in the Prediction of Short- and Long-Term Risks of Stroke After Transient Ischemic Attack

Abstract: Background and Purpose-Several risk scores have been developed to predict the stroke risk after transient ischemic attack (TIA). However, the validation of these scores in different cohorts is still limited. The objective of this study was to elucidate whether these scores were able to predict short-term and long-term risks of stroke in patients with TIA. Methods-From the Fukuoka Stroke Registry, 693 patients with TIA were followed up for 3 years. Multivariable-adjusted Cox proportional hazards model was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
96
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 36 publications
3
96
1
Order By: Relevance
“…Later, many experts make verification on the results of ABCD3 and corresponding ABCD3I. 2,15,17,23,24 Researchers at home and abroad have carried out in accordance with the ABCD3I score validation grouping amount samples of TIA patients into low-risk group (0-3), moderate group (4-7), high-risk group (8 to 13 points) for investigation and study analysis , the results show that the incidence of stroke after TIA within 7 d is: low-risk group < moderate group < high-risk group (differences are statistically significant); Incidence of stroke within 90 d, low-risk group of < moderate group < high-risk groups (the difference had statistical significance), compared with low risk and moderate group, Incidence of stroke within 7 d and 90 d after TIA in high-risk groups were significantly higher, incidence of cerebral infarction within 90 d after TIA in the intermediate risk category is higher than lower dangerous group, the difference was statistically significant. ABCD3I score 8 or more, incidence of stroke within the 7 d after TIA became significantly higher, and when ABCD3I score 4 or more the incidence of stroke points within 90 d after TIA became significantly higher, when ABCD3I score 3 points or less, cerebral infarction was not be found within 7 d, 90 d. It indicates with ABCD3 score higher, there will be possible to become cerebral infarction, indirectly suggest most patients whose ABCD3I score <3 with TIA don't need observation in hospitable, they was medically treated mainly with antiplatelet aggregation of secondary prevention; due to patients with TIA scored 4 to 7 points is the largest number and account for large proportion, they need to be alert to the occurrence of cerebral infarction and if conditions allowed they can be in hospital; Patients scored 8 points or more should be treated as first priority, and should be admitted to hospital as soon as possible and improve the imaging, serology and related inspection and then key intervention and treatment.…”
Section: Abcd3 and Abcd3i Scorementioning
confidence: 99%
See 1 more Smart Citation
“…Later, many experts make verification on the results of ABCD3 and corresponding ABCD3I. 2,15,17,23,24 Researchers at home and abroad have carried out in accordance with the ABCD3I score validation grouping amount samples of TIA patients into low-risk group (0-3), moderate group (4-7), high-risk group (8 to 13 points) for investigation and study analysis , the results show that the incidence of stroke after TIA within 7 d is: low-risk group < moderate group < high-risk group (differences are statistically significant); Incidence of stroke within 90 d, low-risk group of < moderate group < high-risk groups (the difference had statistical significance), compared with low risk and moderate group, Incidence of stroke within 7 d and 90 d after TIA in high-risk groups were significantly higher, incidence of cerebral infarction within 90 d after TIA in the intermediate risk category is higher than lower dangerous group, the difference was statistically significant. ABCD3I score 8 or more, incidence of stroke within the 7 d after TIA became significantly higher, and when ABCD3I score 4 or more the incidence of stroke points within 90 d after TIA became significantly higher, when ABCD3I score 3 points or less, cerebral infarction was not be found within 7 d, 90 d. It indicates with ABCD3 score higher, there will be possible to become cerebral infarction, indirectly suggest most patients whose ABCD3I score <3 with TIA don't need observation in hospitable, they was medically treated mainly with antiplatelet aggregation of secondary prevention; due to patients with TIA scored 4 to 7 points is the largest number and account for large proportion, they need to be alert to the occurrence of cerebral infarction and if conditions allowed they can be in hospital; Patients scored 8 points or more should be treated as first priority, and should be admitted to hospital as soon as possible and improve the imaging, serology and related inspection and then key intervention and treatment.…”
Section: Abcd3 and Abcd3i Scorementioning
confidence: 99%
“…There are foreign scholars scored the large sample TIA patients according to ABCD2, ABCD3, ABCD3I ratings, and were followed up for 3 years, using COX regression model risk proportion to make the comparison to the scoring system, the results also suggest that ABCD3 and ABCD3I scoring system is superior than ABCD2 score on the predictive value of stroke after TIA. 23 Similarly, domestic researchers make a comparison to the moderate amount of samples of TIA patients according to ABCD2, ABCD2I, ABCD3, ABCD3I scoring methods, found that predicting stroke risk within 7 d after TIA, ABCD2, ABCD2I, ABCD3, ABCD3I scoring area under the curve (area under the receiver operating characteristics curve, AUC) are 0.733, 0.898, 0.830 and 0.733 respectively; Predict TIA within 90d after stroke risk was 0.699, 0.857, 0.788 and 0.699respectively, so the study says ABCD3I scoring method is more accurate than ABCD2 and ABCD2I scoring method in predicting TIA back stroke risk, coming with higher clinical value. 25 ABCD, ABCD2and ABCD3 score mainly based on clinical characteristics and are simple, easy, and have a good effect on prediction, but the lack of a TIA etiology, risk factors, imaging and laboratory test, and other auxiliary examination joining, resulting in lacking specificity.…”
Section: Abcd3 and Abcd3i Scorementioning
confidence: 99%
“…The original ABCD score is one of the most famous applicable risk scores [7]. In 2007, Purroy et al [5] suggested a new risk score called ABCD2, then in 2010, Lavallée et al [6] suggested two new risk scores to predict stroke occurrence earlier in time after a patient suffers from TIA.…”
Section: Definition and Motivationmentioning
confidence: 99%
“…The two new risk scores are named ABCD3 and ABCD3-1. As shown in [7] ABCD3-I(c/i) is the best to use in order to predict the occurrence of a stroke using risk factors for TIA Patient during seven days after TIA.…”
Section: Definition and Motivationmentioning
confidence: 99%
See 1 more Smart Citation